K-Pop sebagai Mekanisme Regulasi Emosi pada Remaja - Benedicta Audrey Putri Trisnadewi; Shofwatun Amaliyah (Jurnal Psikologi, 2025)
The K-Pop phenomenon has become an important part of the lives of adolescents in various countries, including Indonesia. Music, concerts, and fandom activities not only serve as entertainment but can also be interpreted as one form of emotional regulation mechanism. This study aims to systematically review the role of K-Pop in supporting adolescent mental health, particularly through the Process Model of Emotion Regulation framework developed by Gross. The study found that adolescents' involvement in K-Pop is closely related to five emotion regulation strategies: situation selection, situation modification, attention deployment, cognitive change, and response modulation. Activities such as listening to K-Pop music, attending concerts, watching online contents, and interacting within fandom communities have been shown to help adolescents divert their attention from stress, build cognitive reinterpretations of negative experiences, and channel emotions adaptively. K-Pop can serve as a significant tool in supporting adolescent mental health, though parental guidance, educator support, and a balanced social environment remain essential to ensure its use is balanced.